Literary Interpretation of Feminism (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article focuses on the rise of feminism in literature, its different stages of development, and the works of writers who contributed to this movement. Feminism sheds light on the character of women, the challenges they face, and how to fight against and overcome these difficulties. Literature plays a crucial role in interpreting such issues and calling for action.